SGCD Homozygous Nonsense Mutation (p.Arg97∗) Causing Limb-Girdle Muscular Dystrophy Type 2F (LGMD2F) in a Consanguineous Family, a Case Report - Younus, Muhammad; Ahmad, Farooq; Malik, Erum; Bilal, Muhammad; Kausar, Mehran; Abbas, Safdar; Shaheen, Shabnam; Kakar, Mohib Ullah; Alfadhel, Majid; Umair, Muhammad (Frontiers in Genetics, 2019)
Background: Limb-girdle muscular dystrophy (LGMD) is an increasingly heterogeneous category of inherited muscle diseases, mainly affecting the muscles of shoulder areas and the hip, segregating in both autosomal recessive and dominant manner. To-date, thirty-one loci have been identified for LGMD including seven autosomal dominant (LGMD type 1) and twenty four autosomal recessive (LGMD type 2) inherited loci. Methodology/ Laboratory Examination: The present report describes a consanguineous family segregating LGMD2F in an autosomal recessive pattern. The affected individual is an 11-year-old boy having two brothers and a sister. Direct targeted next generation sequencing was performed for the single affected individual (VI-1) followed by Sanger sequencing. Results: Targeted next generation sequencing revealed a novel homozygous nonsense mutation (c.289C>T; p.Arg97*) in the exon 3 of the delta-sarcoglycan (SGCD) gene, that introduces a premature stop codon (TCA), resulting in a nonsense mediated decay or a truncated protein product. Discussion and Conclusion: This is the first report of LGMD2F caused by an SGCD variant in a Pakistani population. The mutation identified in the present investigation extends the body of evidence implicating the gene SGCD in causing LGMD2F and might help in genetic counseling, which is more important to deliver the risk of carrier or affected in the future pregnancies.